Droplet spatial distribution of oil-based emulsion spray - Gong, Chen; Chen, Fujun; Cui, Bingbo; Wang, Aichen; Zhang, Zhao; Zhou, Zhenjiang; Liu, Yufei (Frontiers in Plant Science, 2023)
Introduction: Oil-based emulsions solution is a common pesticide formulation in agricultural spraying, and its spray characteristics is different from the water spraying. The well understanding of its spray characteristics is the theoretical basis to improve the pesticide spraying technology. The objective of the presented study is to deepen the understanding of the spray characteristics of oil-based emulsion. Method: In this paper, the spatial distribution characteristics of spray droplets of oil-based emulsion were captured visually using the high-speed photomicrography. Based on image processing method, the droplets size and distribution density of spray droplets at different spatial locations were analyzed quantitatively. The effects of nozzle configuration and emulsion concentration on spray structures and droplets spatial distribution were discussed. Results: Oil-based emulsion produced a special perforation atomization mechanism compared to water spray, which led to the increase of spray droplet size and distribution density. Nozzle configuration had a significant effect on oil-based emulsion spray, with the nozzle changed from ST110-01 to ST110-03 and ST110-05, the sheet lengths increased to 18 mm and 28 mm respectively, while the volumetric median diameters increased 51.19% and 76.00% respectively. With emulsion concentration increased from 0.02% to 0.1% and 0.5%, the volumetric median diameters increased 5.17% and 14.56% respectively. Discussion: The spray droplet size of oil-based emulsion spray can be scaled by the equivalent diameter of discharge orifice of nozzles. The products of volumetric median diameters and corresponding surface tensions were nearly constant for the oil-based emulsion spray of different emulsion concentrations. It is expected that this research could provide theoretical support for improving the spraying technology of oil-based emulsion and increasing the utilization of pesticide.